What does it mean to correct the scientific record? A case study of the JACS (2000-2023) - Bordignon, Frédérique (2023)
This paper examines how the Journal of the American Chemical Society (JACS) displays notices of correction and retraction, and how their status is reflected across various venues. With a corpus of 1083 editorial notices, we first show that even on the JACS website, the original source, there are mistakes and inaccuracies. Additionally, our study demonstrates some improvements in certain contexts in comparison to earlier studies, as well as significant variations between platforms (bibliographic databases and open access archives). But it also reveals that the same types of issues still remain, including the lack of accurate information close to the updated publications, and the lack of a two-way link between notices and original publications. This preliminary research seeks to provide an overview of what constitutes the scientific record and what it means to correct it, in order to avoid the spread of unsubstantiated claims by ill-informed readers.